2017
DOI: 10.1038/s41598-017-00821-5
|View full text |Cite
|
Sign up to set email alerts
|

RNA sequence analysis of rat acute experimental pancreatitis with and without fatty liver: a gene expression profiling comparative study

Abstract: Fatty liver (FL) is one of the risk factors for acute pancreatitis and is also indicative of a worse prognosis as compared to acute pancreatitis without fatty liver (AP). The aim of the present study was to analyze, at the hepatic level, the differentially expressed genes (DEGs) between acute pancreatitis with fatty liver (APFL) rats and AP rats. GO (Gene Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) pathway analyses of these DEGs indicated that PPARα signalling pathway and fatty acid degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…RNA sequencing is a useful technology with an advantage in discovering novel tissue-and disease-specific ncRNAs, whereas microarray and qRT-PCR can only measure the expression levels of known ncRNAs 10 , 16 . To date, RNA sequencing has been widely used in transcriptome profiles analyses 17 .…”
Section: Introductionmentioning
confidence: 99%
“…RNA sequencing is a useful technology with an advantage in discovering novel tissue-and disease-specific ncRNAs, whereas microarray and qRT-PCR can only measure the expression levels of known ncRNAs 10 , 16 . To date, RNA sequencing has been widely used in transcriptome profiles analyses 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Among them, PPAR signaling was an extremely important pathway. The PPAR signaling pathway has been considered to be related to the pathological processes of fatty liver development in rats with acute pancreatitis [ 17 ]. PPARA was a nuclear hormone receptor and important regulator of lipid metabolism in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…High triglyceride level is also a risk factor, serum triglyceride level higher than 5.6 mmol/L significantly increases the mortality rate (OR = 2.75, 95% CI = 1.28–5.92, p < 0.01) [ 16 ]. An experimental study in rat AP model demonstrated that the presence of FLD increased pro-inflammatory cytokine production, which may worsen the course of the disease [ 17 ]. Cross-sectional studies confirmed that AP is often accompanied by FLD, with a prevalence between 18–43% [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%